2020
DOI: 10.1002/ppp.2030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ice‐wedge activity over 25 years of climate change near Salluit, Nunavik (northern Québec, Canada)

Abstract: To assess the direct impact of climate change on ice‐wedge (IW) degradation, 16 sites in the Narsajuaq river valley (Nunavik, Canada) that were extensively studied between 1989 and 1991 were revisited in 2016, 2017 and 2018. In total, 109 pits were dug to record soil characteristics and IW shapes and depths. Changes in surface conditions were also noted using side‐by‐side comparisons of recent (2017) and older (1989–1991) land and aerial photographs. During the past 25 years, the active layer reached depths th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Vegetation in the valley is mostly composed of deciduous shrubs (14.6%), graminoids (32.1%), or a mix of both (33.3%). The remaining 5.9% is a mix of mosses, Sphagnum sp., evergreen shrubs, forbs, and lichens 26 …”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation in the valley is mostly composed of deciduous shrubs (14.6%), graminoids (32.1%), or a mix of both (33.3%). The remaining 5.9% is a mix of mosses, Sphagnum sp., evergreen shrubs, forbs, and lichens 26 …”
Section: Study Sitementioning
confidence: 99%
“…Most notably, between 1989 and 1991, Kasper and Allard 10,14 investigated ice‐wedge activity and morphology using field observations in the Narsajuaq river valley near Salluit, Nunavik, Canada. In 2016, 2017 and 2018, Gagnon and Allard 26 revisited the same 16 study sites to investigate the impact of climate change on winter soil cracking frequency and morphology of ice‐wedge tops. They found that based on the depth of ice‐wedge tops, the active layer had sometime in the period reached depths that were 1.2–3.4 times greater than in 1991, which led to the widespread degradation of ice‐wedge tops in the valley.…”
Section: Introductionmentioning
confidence: 99%
“…Annual precipitation totals 524 mm, about half consisting of snowfall (Charron 2015). Most of the valley floor is covered by graminoids (sedges, grasses, and rushes) (32.1%), low deciduous shrubs (14.6%), and a mix of both (33.3%) (Gagnon and Allard 2020a). The rest of the vegetation cover is a mix of mosses, evergreen shrubs, forb species, and lichens.…”
Section: Geomorphological Heritage From the Holocene And Characteristmentioning
confidence: 99%
“…During the summers of 2016 and 2017, 16 sites with polygonal networks were investigated ( Fig. 2) (Gagnon and Allard 2020a). The sites are located on different terrace levels in the valley and have varying soil compositions, vegetation covers, and surface drainage conditions (see Gagnon and Allard 2020a).…”
Section: Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation